2019
DOI: 10.1111/jocn.14963
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mathematics self‐efficacy on numeracy performance in first‐year nursing students: A quasi‐experimental study

Abstract: Aim and objectives To examine the factors that influence nursing students’ mathematics self‐efficacy, the effect of numeracy instruction on self‐efficacy, and the association between self‐efficacy and numeracy test performance. Background Medication administration errors, including administering incorrect dosages or infusion rates, can result in serious harm to patients. Hence, it is essential that nursing students are adequately prepared with the necessary numeracy skills during their nursing program. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Demographic factors of nursing students are used in educational research to identify the makeup of the sample population but are rarely researched for relevance. Studies that were researched in the literature review did not show any statistically significant improvement in dosage calculation scores in relation to a nursing students age (Fusco et al, 2021;Gregory et al, 2019;Kuo et al, 2020).…”
Section: Research Questionmentioning
confidence: 93%
See 2 more Smart Citations
“…Demographic factors of nursing students are used in educational research to identify the makeup of the sample population but are rarely researched for relevance. Studies that were researched in the literature review did not show any statistically significant improvement in dosage calculation scores in relation to a nursing students age (Fusco et al, 2021;Gregory et al, 2019;Kuo et al, 2020).…”
Section: Research Questionmentioning
confidence: 93%
“…Studies that were researched in the literature review did not show any statistically significant improvement in dosage calculation scores in relation to a nursing students' gender (Fusco et al, 2021;Gregory et al, 2019;Kim & Lee, 2020;Kuo et al, 2020). The literature review did find that age and gender demographics of nursing students play a role in increased satisfaction with learning and improved self-confidence (Dincer & Ataman, 2020;Gregory et al, 2019;Kim & Lee, 2020;Kuo et al, 2020).…”
Section: Research Questionmentioning
confidence: 96%
See 1 more Smart Citation
“…Findings from this work provide support for Bandura's component of how performance achievement effects self-efficacy. Gregory et al (2019) found structured interventions and instruction significantly improved students' self-efficacy in math. [13] The increase in math self-efficacy was associated with positive math performance.…”
Section: Introductionmentioning
confidence: 93%
“…Gregory et al (2019) found structured interventions and instruction significantly improved students' self-efficacy in math. [13] The increase in math self-efficacy was associated with positive math performance. Nursing educators need to determine educational strategies that will help students achieve self-efficacy and become competent in MDC.…”
Section: Introductionmentioning
confidence: 93%